Forensic genetic polymorphisms and population structure of the Guizhou Bouyei people based on 19 X-STR loci - Zheng Ren; Jianxin Guo; Guanglin He; Han Zhang; Xing Zou; Hongling Zhang; Qiyan Wang; Jingyan Ji; Meiqing Yang; Jing Zhang; Ziqian Zhang; Yilizhati Nabijiang; et al. (Taylor & Francis Group, 2019)
Background: Guizhou province is located in southwest China with abundant genetic, linguistic and cultural diversity. The Bouyei is one of the 18 officially recognised minority groups in Guizhou, accounting for about 97% of the total Bouyei population in China. However, the genetic history and forensic characterisation of the Bouyei people is largely unknown due to a lack of genetic data. Aim: We aim to investigate genetic polymorphisms and forensic characterisation of the Guizhou Bouyei population, as well as the relationships between the Bouyei and other East Asian populations. Subjects and methods: We genotyped 19 X-STRs in 188 males and 165 females of Guizhou Bouyei using the AGCU X19 STR Kit. We estimated allele frequencies, forensic parameters and genetic distances between the Bouyei and other East Asian populations. We presented the genetic distances in a phylogenetic tree, an MDS plot and a PCA plot. Results: In Guizhou Bouyei individuals, we observed 216 alleles with corresponding frequencies ranging from 0.0019 to 0.6757. All of the six combined powers of PDm, PDf, MEC Krüger, MEC Kishida, MEC Desmarais and MEC Desmarais in allele diversity and haplotype diversity are larger than 0.99999995. We found genetic affinities among the Bouyei people and their geographical neighbouring populations in Guizhou, such as the Sui, Miao and Han. Conclusions: The highly polymorphic and informative forensic parameters of the 19 X-STRs in Bouyei people show the powerful potential of those markers in forensic identification and parentage tests. The genetic relationships of the Bouyei with other East Asian populations correspond well with geographic affiliations as well as linguistic classifications.